Rayleigh lidar measurements of the middle atmosphere above Kingston, Australia - KLEKOCIUK, ANDREW (hasPrincipalInvestigator); KLEKOCIUK, ANDREW (processor); Australian Antarctic Data Centre (publisher)
Vertical Rayleigh lidar measurements of the middle atmosphere above Kingston, Australia were undertaken during development of a lidar system that became operational at Davis, Antarctica on 07 Feb 2001. The lidar was operated sporadically at Kingston between 1997 and 2000. Data collected during observing sessions on 47 separate days have been analysed to produce average profiles of temperature, density and backscatter ratio (at 532nm wavelength). The standard Rayleigh lidar inversion technique has been applied, using radiosonde data from Hobart Airport to calibrate the lidar density profiles near 30km altitude. Corrections for instrumental effects (pulse pileup, shutter transmission) and extinction (including ozone) have been applied. Where available, the temperature retrieval process has been initialised with UARS HALOE and MLS measurements. The typical integration time and altitude binning of the raw data were 1 minute and 94 metres respectively. Processed data have been produced at a variety of resolutions for investigation of gravity wave activity. This analysis is ongoing. The lower altitude limit of the aerosol data are approximately 15km, while the lower limit of the temperature data are about 30km. For more information, see the metadata record entitled 'Lidar Studies of Atmospheric Structure, Dynamics and Climatology'.